Behavior of Self-Compacting Concrete with Different Fineness Moduli of Fine Aggregate - Ali, Ahmed Sultan (Al-Nahrain Journal for Engineering Sciences, 2017)
The main objective of the present paper is to investigate the effect of fineness moduli (FM) of fine aggregate on fresh properties (flow ability. Passing ability and segregation resistance), and hardened properties (compressive strength, split tensile strength, flexural strength and ultrasonic pulse velocity UPV) of self-compacting concrete (SCC). Four values of FM 2.3, 2.5, 2.7 and 3.1 were used, according to acceptance range of ASTM C33-03 for FM for fine aggregate, which recommended range for FM is 2.3 to 3.1._x000D_ Four series of mixes were casting , each series consist of two mixes represent normal strength and high strength SCC, each series of mixes made from fine aggregate have the same FM. Flow ability, passing ability.and segregation resistance of fresh SCC, both with normal and high strength decreases with increasing the fineness moduli. High strength SCC more effected than normal strength concrete due to increase the volume of particles. _x000D_ Great enhancement in compressive strength split tensile strength and flexural strength in both normal and high strength SCC when the FM is 2.5. Increase FM to 2.7 and 3.1 not lead to increase in strengths. The UPV values of normal and high strength SCC mixes have a good general condition. SCC mixes with FM 2.5 possess excellent general conditions.